Using Virtual Reality in the Treatment of Social Anxiety Disorder: Technological Proposal - Ramos-Galarza, Carlos (2021)
The treatments for anxiety that have proven efficacy are based on cognitive behavioral therapy, this time we will focus on systematic desensitization, which aims to expose the subject successively to the element that generates the maladaptive response, with this purpose a technological application is proposed for the treatment of this disorder from virtual reality. To accomplish this goal, an electronic helmet where different scenarios will be projected is going to be used. The person who is wearing it will face the distressing stimuli, allowing the treatment of his/her anxiety. With this application and device, it will be possible to safeguard the physical and psychic integrity of the subjects that demand this type of attention.